Community-based Health Planning and Services programme in Ghana: a systematic review - Adusei, Abena Boahemaa; Bour, Helen; Amu, Hubert; Afriyie, Augustine (Frontiers in Public Health, 2024)
Introduction Ghana established Community-based Health Planning and Services (CHPS) as the primary point of contact for primary healthcare in 1999. CHPS has since emerged as the country’s primary strategy for providing close-to-client healthcare delivery, with numerous positive health outcomes recorded as a result of its implementation. There is, however currently a paucity of systematic reviews of the literature on CHPS. The purpose of this study was not only to investigate dominant trends and research themes in Community-based Health Planning and Services, but also to track the evolution of the CHPS intervention from its inception to the present. Method We adopted a systematic review approach for selected articles that were searched on Google Scholar, PubMed, and Scopus databases. The study was conducted and guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. We then applied a reflexive thematic analysis approach in synthesizing the results. Results The search resulted in 127 articles of which 59 were included in the final review. Twenty (20) papers targeted the national level, eighteen (18) for the regional level, sixteen (16) for the district level, two (2) for the sub-district level, and three (3) papers targeted the community. The years 2017 and 2019 were recorded to be the years with the highest number of publications on CHPS in Ghana. Conclusion Community-based Health Planning and Services (CHPS) is an effective tool in addressing barriers and challenges to accessing quality and affordable health care causing significant effects on health. It provides close-to-client healthcare delivery in the community.